ANALYSIS OF ARABICA COFFEE CHARACTERISTICS AND DRYING METHOD ON ARABICA COFFEE FLAVOR USING ANALYSIS OF VARIANCE - Sumitro, Martinus Robinson; Hutabarat, Julianus; Achmadi, Fuad (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2025)
This study investigated the effect of the coffee drying process using a coffee drying house on the moisture content, acidity, caffeine value, and flavour of Arabica coffee. An experimental method with a two-factor analysis of variance was used to evaluate significant differences between three different drying processes: Before Drying Process, Sun Drying Process, and Drying Process with Coffee Drying House. The results showed that sun-drying coffee with a coffee drying house produced lower moisture content, acidity, and caffeine value than the other drying processes. The flavour of Arabica coffee produced by this method was also considered sweeter by coffee export standards. Statistical analysis with Anova Block Subsampling, Anova 1 Factor Fixed Model, and Anova 2 Factor Factorial Design showed that the coffee drying process using coffee drying houses significantly affects the quality of arabica coffee. This study concludes that coffee drying houses can be an effective solution in improving the quality of Arabica coffee by controlling the moisture content, acidity, and caffeine value. The results of this study contribute to understanding the process of drying coffee beans and the factors that affect the final quality of the product. Therefore, this study provides an essential scientific basis for coffee farmers and the coffee processing industry to improve the quality of their coffee.